8-hydroxypinoresinol-4-O-β-D-glucoside from Valeriana officinalis L. Is a Novel Kv1.5 Channel Blocker. (10th August 2021) - Liu, Xingxing; Duan, Xueyun; Fan, Heng; Wang, Hongfei; Jiang, Xionggang; Fang, Ying; Tang, Qing; Xiao, Jun; Li, Qian
Abstract: Ethnopharmacology relevance: In folkloric medicine of many cultures, one of the medical uses of Valeriana officinalis Linn is to treat heart-related disease. Recently, it was shown that the ethanol extracts from V. officinalis could effectively prevent auricular fibrillation, and 8-hydroxypinoresinol-4-O-β-D-glucoside (HPG) from the extracts is one of the two active compounds showing antiarrhythmia activities. Aim of the study: The human Kv1.5 channel (hKv1.5) has potential antiarrhythmia activities, and this study arms at investigating the current blocking effects of HPG on hKv1.5 channel. Material and methods: HPG was obtained from V. officinalis extracts, and hKv1.5 channels were expressed in HEK 293 cells. HPG was perfused while recording the current through hKv1.5 channels. Patch-clamp recording techniques were used to study the effects of HPG at various concentrations (10 μM, 30 μM, and 50 μM) on hKv1.5 channels. Results: The present study demonstrated that HPG inhibited hKv1.5 channel current in a concentration-dependent manner; the higher the concentration, the greater is the inhibition at each depolarization potential. During washout, the channels did not full recover indicating that the un-coupling between HPG and hKv1.5 channels is a slow process. Conclusion: HPG may be an effective and safe active ingredient for AF having translational potential. Graphical abstract: Image 1